Retirement intentions in the presence of technological change: Theory and evidence from France - Pierre-Jean Messe; Eva Moreno-Galbis; Francois-Charles Wolff (IZA Journal of Labor Economics, 2014)
This paper investigates the role of productivity as a determinant of the worker's retirement intentions. Using an overlapping generation framework, we analyze the retirement decision of a cohort of workers being ability heterogeneous. The labor market is endogenously segmented between workers having the required ability level to occupy jobs where the productivity is indexed to the technological state via on-the-job training (complex jobs) and the rest of workers, who are employed in positions where productivity is relatively deteriorated in case of technological change due to the absence of on-the-job training (simple jobs). In case of technological change, workers in complex jobs delay their retirement date, whereas workers in simple positions will not modify their retirement decision unless taxes change. Using data from France, we find that after a technological change, older workers who benefit from a skill upgrading training program have a higher intended retirement age.
Keywords: J14; J22; J24; J26; 330; OLG; Retirement intentions; Technological change; Training